Irregular Microdome Structure‐Based Sensitive Pressure Sensor Using Internal Popping of Microspheres. (30th March 2022) - Jung, Young; Choi, Jungrak; Lee, Wookjin; Ko, Jong Soo; Park, Inkyu; Cho, Hanchul
Abstract: Modifying the surface morphology of an elastomer surface into 3D microstructures is crucial for various soft sensor applications. However, processes based on typical mold microfabrication and elastomer casting remain the dominant methodologies. This study demonstrates a novel strategy for generating 3D and irregular microdome structures for flexible pressure sensors through the internal popping of microspheres. When thermal treatment is applied to a composite film composed of microspheres and an elastomer matrix, the microspheres expand, and irregular microdome structures are generated. This composite film with an irregular microdome structure is utilized as a piezoresistive pressure‐sensing film. The sensor shows high sensitivity (−50.45 kPa −1 ) owing to the heterogeneous contact change between the irregular microdome structure and a laser‐induced graphene electrode; it also exhibits a short response time (τ10‐90%  ≈ 39 ms), excellent repeatability, and high reliability. The sensor is applied in a fingertip‐shaped pressure sensor to detect the blood pulse on the index finger and on electronic skin to recognize soft objects. Furthermore, a pressure sensor array that enables various functions such as drawing, multitouch, and deep learning‐based motion control, is demonstrated. Abstract : An irregular microdome structure with a design and manufacturing flexibility is generated by internal popping of microspheres. By integrating this structure with a laser‐induced graphene electrode, a large scale pressure sensor with excellent sensing performances such as high sensitivity (−50.45 kPa −1 ), short response time (τ10‐90%  ≈ 39 ms), and high reliability (stable sensor response under 1 kPa and 4000 cycles) is realized.